2021
DOI: 10.2174/2211352518999200520081129
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ESBL-Producing Gram-Negative Bacteria of Lower Respiratory Tract Infection in Bharatpur Hospital, Nepal

Abstract: Background: Antimicrobial resistance is a global threat in the medical society. Extended-Spectrum β-lactamase (ESBL) producing bacteria are increasing worldwide including Nepal and causing more severe infections because of their continuous mutation and multidrug resistance (MDR) nature. Objective: The objective of this study was to assess Gram-negative bacterial etiology of lower respiratory tract infections (LRTIs) and determine their antibiotic susceptibility pattern with a special focus on MDR including E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several studies in Nepal have reported the prevalence of MDR [ 22 , 23 ] and ESBL producers [ 8 10 ]. Despite knowing the fact, in Nepal, the literature regarding ESBL production among MDR isolates and their responsible genes are poorly stated than other developed nations; the present study would help to investigate the prevalence of CTX-M β -lactamases producing MDR E. coli and K. pneumoniae among patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in Nepal have reported the prevalence of MDR [ 22 , 23 ] and ESBL producers [ 8 10 ]. Despite knowing the fact, in Nepal, the literature regarding ESBL production among MDR isolates and their responsible genes are poorly stated than other developed nations; the present study would help to investigate the prevalence of CTX-M β -lactamases producing MDR E. coli and K. pneumoniae among patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although ESBL was discovered several decades ago, there have been troublesome to sort out organisms that are responsible for ESBL production due to several reasons such as difficulty in its detection and variability during reporting [7]. A large number of studies have reported the presence of ESBL producers in clinical [8][9][10] as well as nonclinical samples [11][12][13]. Nevertheless, some studies concluded E. coli and K. pneumoniae as the most crucial bacteria responsible for ESBL production [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa has great diversity and is capable of causing life-threatening contagious infections in a multifariousness patients' population [10], causing several diseases such as urinary tract infections (UTIs) [11], respiratory tract infections (RTIs) [12], burn wounds, skin and soft tissue infections [13], bacterial keratitis [14], and swimmer ear infections [15].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to the different classes of antibiotics by P. aeruginosa is due to the loss or reduced copy numbers of oprD and overproduction of active efflux pumps, AmpC β-lactamase and extended-spectrum β-lactamases and their resistance mechanism are classified as intrinsic, acquired, and adaptive [6]. In Nepal, the increasing trend of antimicrobial-resistance bacteria in both clincal and nonclinical settings [11,12,[20][21][22][23][24][25][26] is becoming an alarming health issue. ere is no exact observable scheme for marking antibiotic resistance patterns and their use in Nepal.…”
Section: Introductionmentioning
confidence: 99%